Endoscopic surveillance with systematic random biopsy for the early diagnosis of hereditary diffuse gastric cancer: a prospective 16-year longitudinal cohort study. Issue 1 (January 2023) - Lee, Colin Y C; Olivier, Adriaan; Honing, Judith; Lydon, Anne-Marie; Richardson, Susan; O'Donovan, Maria; Tischkowitz, Marc; Fitzgerald, Rebecca C; di Pietro, Massimiliano
Summary: Background: Hereditary diffuse gastric cancer, generally caused by germline pathogenic variants in CDH1, presents with early-onset signet ring cell carcinoma. Prophylactic total gastrectomy is the definitive treatment. Endoscopic surveillance can inform the timing of prophylactic total gastrectomy through detection of microscopic signet ring cell carcinoma foci. However, evidence is scarce about the optimal endoscopic sampling technique and characterisation of signet ring cell carcinoma foci in hereditary diffuse gastric cancer. We aimed to formally assess the diagnostic yield of different sampling strategies and to identify criteria for the characterisation of endoscopic lesions. Methods: For this prospective longitudinal cohort study, we included individuals aged 18 years or older at the Cambridge University Hospitals National Health Service (NHS) Foundation Trust who fulfilled testing criteria for hereditary diffuse gastric cancer between June 1, 2005, and July 31, 2021. The primary outcome was detection of intramucosal signet ring cell carcinoma foci. We assessed the detection rate and anatomical location of signet ring cell carcinoma in random biopsy samples taken according to a systematic protocol compared with biopsies targeted to endoscopic findings. Endoscopic lesions were examined with white-light and narrow band imaging with magnification to assess the likelihood of cancerous foci. Findings: 145 individuals were included, of whom 68 (47%) were male and 92 (63%) carried the CDH1 pathogenic variant. 58 (40%) patients were diagnosed with invasive signet ring cell carcinoma over a median follow-up time of 51 months (IQR 18–80). The first diagnosis of signet ring cell carcinoma was most commonly made from random biopsies (29 [50%] of 58 patients), rather than targeted biopsies (15 [26%] patients). The anatomical distribution of signet ring cell carcinoma foci detected by random biopsies more accurately reflected those identified in prophylactic total gastrectomy specimens than did targeted biopsies. Omitting random biopsies in our cohort would have led to an under-diagnosis rate of 42%. Using a novel panel of endoscopic criteria, gastric lesions containing signet ring cell carcinoma were predicted with a sensitivity of 67·3% and a specificity of 90·2%. Interpretation: Random biopsies enhance the early detection of signet ring cell carcinoma and are complementary to targeted biopsies in surveillance of hereditary diffuse gastric cancer. This sampling method should be the standard of care when performing all surveillance endoscopies for individuals with hereditary diffuse gastric cancer. Funding: UK Medical Research Council.